Effect of ultrasound combined with plasma protein treatment on the structure, physicochemical and rheological properties of myofibrillar protein - Ye Zou; Lingjuan Wang; Xiaowen Wang; Yibo Lan; Jingjing Ma; Jing Yang; Weimin Xu; Qi Shen; Daoying Wang (Ultrasonics Sonochemistry)
This study aimed to investigate the effect of ultrasound combined with plasma protein (UPP) treatment on the structure, physicochemical and rheological properties of myofibrillar protein (MP). The results indicated that the UPP group caused changes in the secondary structure, increased fluorescence intensity and enhanced surface hydrophobicity of MP. Then, UPP significantly decreased the content of free and total sulfhydryl group, and high molecular weight protein contents were observed in MP. These findings implied moderate cross-linking and aggregation between plasma protein and MP in this ultrasound treatment. Furthermore, the physical characteristics, stability and rheological properties of MP were improved in UPP, as evidenced by increased storage modulus and decreased loss angle tangent. Therefore, this study suggested that the combined treatment not only had the potential to enhance the product quality in the process of ground meat, but also improved the utilization rate and added value of plasma proteins.